DEVELOPMENT AND VALIDATION OF A HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR ASSAY DETERMINATION OF ERLOTINIB HCL IN TABLET DOSAGE FORM - Susanti Larasati, Tri
Erlotinib HCl is a compound widely used in the treatment of non-small cell lung cancer (NSCLC) and pancreatic cancer. The determination of Erlotinib levels in tablet formulations is essential to ensure the ef icacy and safety of the medication. The development of this analysis method was carried out using a Waters HPLC instrument with a stationary phase consisting of a L7 4.6 x 250 mm, 5 ?m (Zorbax) column, an isocratic mobile phase of pH 3 buf er and acetonitrile (72:28), a column temperature of 30°C, UV-Vis detector at a wavelength of 247 nm, and a flow rate of 1.5 mL/min. Optimization of sonication time and filter compatibility was performed before the analysis method validation. Sonication time optimization was conducted by examining the Erlotinib HCl content in tablets with variations of 5 minutes, 10 minutes, and 30 minutes, resulting in 102.7%, 102.1%, and 102.9% recoveries, respectively, with no dif erence in results between each time. Filter compatibility optimization was carried out using variations of PVDF, PTFE, Nylon, and RC filters with comparison solution, yielding % recoveries between filters of 99.4%, 99.4%, 100.6%, and 100.4%, respectively.Validation of the analysis method was conducted according to ICH Q2 and USP guidelines, covering parameters such as specificity, linearity, accuracy, precision, and robustness (solution stability). The validation results showed that the developed HPLC method can provide a specific, linear, accurate, and precise method for analyzing Erlotinib HCl in tablet formulations, with no solvent and placebo interference at the Erlotinib retention time, an average % recovery for 3 concentration levels of 70-130% of 101.2%, and % RSD for 9 accuracy data and % RSD for 12 data with analyst, instrument, and laboratory dif erences of 0.3% and 1.7%, respectively. Based on the research, the variation in buf er pH shows that within the pH range of 2.8-3.2, the critical parameter results are still within acceptable limits. Additionally, the results of standard solution and sample solution stability showed stability for 24 hours at room temperature. Based on the results of method development and validation, it can be concluded that the analysis method is valid for quality control purposes and regulatory compliance.